Genetically modified plants : assessing safety and managing risk - Tzotzos, George T.; Head, Graham Philip; Hull, Roger (Academic Press, 2009)
A transgenic organism is a plant, animal, bacterium, or other living organism that has had a foreign gene added to it by means of genetic engineering. This book provides the basic information for a wide range of people involved in the release of transgenic crops. It details mitigation techniques for human and environmental effects.